Association of the areas over and under the lymphocyte curve with cytomegalovirus reactivation after allogeneic hematopoietic stem cell transplantation. Issue 1 (16th September 2020) - Kimura, Shun‐ichi; Nakamura, Yuhei; Kawamura, Masakatsu; Takeshita, Junko; Kawamura, Shunto; Yoshino, Nozomu; Misaki, Yukiko; Yoshimura, Kazuki; Matsumi, Shimpei; Gomyo, Ayumi; Akahoshi, Yu; Tamaki, Masaharu; et al.
Abstract: Background: We retrospectively compared the impact of the areas over and under the lymphocyte curve (L_AOC vs L_AUC) on cytomegalovirus (CMV) reactivation after allogeneic hematopoietic stem cell transplantation (HSCT). Methods: Among 394 consecutive patients who underwent their first allogeneic HSCT at our center between 2007 and 2018, 301 patients met the inclusion criteria. L_AOC was calculated as the area over the lymphocyte curve during lymphopenia (absolute lymphocyte count [ALC] <700/μL). We calculated L_AOC and L_AUC from day 0 to day 15 (L_AOC15, L_AUC15) and from day 0 to day 30 (L_AOC30, L_AUC30). Results: CMV antigenemia was defined as more than 3 cells/2 slides by the C10/11 method and detected in 204 cases (CMV reactivation) at a median of 39 days after HSCT. Although there were significant differences in L_AOC15, L_AOC30, L_AUC15, and L_AUC30 between patients with and without CMV reactivation, there was no difference in accuracy for predicting CMV reactivation between L_AOC and L_AUC. In a multivariate analysis, L_AOC15 and L_AUC15 were each identified as independent predictive factors for CMV reactivation, along with advanced age and CMV serostatus. However, ALC at day 14 or day 21 was as accurate as area‐based indexes such as L_AOC15 and L_AUC15. L_AOC15 and L_AUC15 were significantly associated with longer duration of anti‐CMV antiviral therapy while ALC was not. Conclusions: L_AOC15 and L_AUC15 had similar impacts on CMV reactivation. Although these area‐based indexes were not superior to ALC for predicting CMV reactivation, they might predict patients who need longer duration of antiviral therapy more accurately.